The Double Edge of Legitimacy: How Women with Disabilities Interpret Good Mothering. (April 2019) - Frederick, Angela; Leyva, Kylara; Lavin, Grace
Modern ideologies of "good mothering" demand the resources and family configurations primarily available to privileged mothers, and mothers with disabilities are among those women who have been regarded as unsuitable for the responsibilities demanded of mothers in advanced industrial societies. Although less often explored than dynamics of race and class, mothers with disabilities are among those women who have been regarded as unsuitable for the responsibilities demanded of mothers in advanced industrial societies. Through interviews and focus groups conducted with mothers who have sensory and/or physical disabilities, we examine how women with disabilities interpret their identities as mothers in relation to modern ideals of good mothering. We find that motherhood offered some participants a path to feminine legitimacy often denied women with disabilities. Yet, because they are simultaneously regarded as less-than-ideal mothers, participants engaged in interpretive strategies including upholding and expanding dominant standards of good mothering, as well as reframing and rejecting elements of this mothering logic. We also find that, like women of color, these mothers engaged in culturework, performing identity work to strengthen their children's social justice perspectives on disability and other forms of inequality.